Fe3O4@Au composite magnetic nanoparticles modified with cetuximab for targeted magneto-photothermal therapy of glioma cells - Lu Q (Dove Medical Press, 2018)
Qianling Lu,1,* Xinyu Dai,1,* Peng Zhang,1,* Xiao Tan,2 Yuejiao Zhong,3 Cheng Yao,4 Mei Song,4 Guili Song,4 Zhenghai Zhang,4 Gang Peng,5 Zhirui Guo,6 Yaoqi Ge,7 Kangzhen Zhang,7 Yuntao Li7 1Department of Neurology, Second Affiliated Hospital of Nanjing Medical University, Nanjing, China; 2Department of Emergency, Second Affiliated Hospital of Nanjing Medical University, Nanjing, China; 3Department of Oncology, The Affiliated Cancer Hospital of Nanjing Medical University, Nanjing, China; 4Office of Academic Research, Kizilsu Kirghiz Autonomous Prefecture People’s Hospital, Atush, China; 5Department of Neurosurgery, Second Affiliated Hospital of Nanjing Medical University, Nanjing, China; 6Department of Geratology, Second Affiliated Hospital of Nanjing Medical University, Nanjing, China; 7Department of General Practice, Second Affiliated Hospital of Nanjing Medical University, Nanjing, China *These authors contributed equally to this work Background: Thermoresponsive nanoparticles have become an attractive candidate for designing combined multimodal therapy strategies because of the onset of hyperthermia and their advantages in synergistic cancer treatment. In this paper, novel cetuximab (C225)-encapsulated core-shell Fe3O4@Au magnetic nanoparticles (Fe3O4@Au-C225 composite-targeted MNPs) were created and applied as a therapeutic nanocarrier to conduct targeted magneto-photothermal therapy against glioma cells. Methods: The core-shell Fe3O4@Au magnetic nanoparticles (MNPs) were prepared, and then C225 was further absorbed to synthesize Fe3O4@Au-C225 composite-targeted MNPs. Their morphology, mean particle size, zeta potential, optical property, magnetic property and thermal dynamic profiles were characterized. After that, the glioma-destructive effect of magnetic fluid hyperthermia (MFH) combined with near-infrared (NIR) hyperthermia mediated by Fe3O4@Au-C225 composite-targeted MNPs was evaluated through in vitro and in vivo experiments. Results: The inhibitory and apoptotic rates of Fe3O4@Au-C225 composite-targeted MNPs-mediated combined hyperthermia (MFH+NIR) group were significantly higher than other groups in vitro and the marked upregulation of caspase-3, caspase-8, and caspase-9 expression indicated excellent antitumor effect by inducing intrinsic apoptosis. Furthermore, Fe3O4@Au-C225 composite-targeted MNPs-mediated combined hyperthermia (MFH+NIR) group exhibited significant tumor growth suppression compared with other groups in vivo. Conclusion: Our studies illustrated that Fe3O4@Au-C225 composite-targeted MNPs have great potential as a promising nanoplatform for human glioma therapy and could be of great value in medical use in the future. Keywords: Fe3O4@Au-C225 composite-targeted magnetic nanoparticles, U251 cells, human glioma therapy, magnetic fluid hyperthermia, near-infrared hyperthermia